Strategi Penyaluran Dana Zakat Baznas di Desa Pamenang Melalui Program Pemberdayaan Ekonomi - Ardiyansah Ardiyansah; Elyanti Rosmanidar; Erwin Saputra Siregar (Jurnal Inovasi Ekonomi Syariah dan Akuntansi, 2024)
Poverty in Indonesia is something that is familiar to encounter in developing countries, one of which is Indonesia. Underdevelopment is a portrait of most of the Indonesian people, the majority of whom are Muslims, one of whom is in Pamenang Village. As for the object that is used as a data source for this research, the BAZNAS strategy for economic empowerment in Pamenang Village. By using these two strategies, the authors argue that there has been significant progress in the economic empowerment managed by the Pamenang village BAZNAS. Based on the results of the research, the author stated that Baznas had succeeded in running the Economic Empowerment Strategy Program in Pamenang Village by reducing the poor population in Pamenang village.